A retrospective evaluation of shortened-duration oral N-acetylcysteine for the treatment of acetaminophen poisoning - Betten, David P.; Burner, Elizabeth E.; Thomas, Stephen C.; Tomaszewski, Christian; Clark, Richard F. (Journal of medical toxicology, 2009)
Introduction The use of less than the traditional 72-hour course of oral N-acetylcysteine has been an alternative treatment option following potentially toxic acute and chronic acetaminophen ingestions felt to be at low risk of developing hepatotoxicity. While clinical experience with shortened treatment duration is extensive, there are few studies evaluating the effectiveness and extent to which these regimens may be used. Methods A large statewide poison center database was reviewed for all acetaminophen exposures involving potentially toxic acute and chronic ingestions, in addition to those taking place at unknown times. Patients were identified who met laboratory criteria for early N-acetylcysteine (NAC) discontinuation (APAP < 10 μm/mL, INR ≤ 1.3, and AST/ALT ≤ 60 IU) after a minimum of a 140-mg/kg oral NAC loading dose and 5 additional 70-mg/kg doses over 20 hours. A further search of the poison center database was conducted for individuals who received shortened-course (20–48 hours) oral NAC treatment who developed subsequent hepatotoxicity or death. Results Of 3303 individuals with potentially toxic acetaminophen ingestions, 1932 met criteria for early NAC discontinuation. Mean treatment duration was 36.4±7.7 hours (acute=37.3±7.6 hours; chronic=34.8±7.4 hours; unknown=35.2±7.6 hours). The poison center database search identified no short-course eligible subjects who developed subsequent hepatotoxicity or death following ≤48 hours of oral NAC. Conclusion Treatment with shortened-course oral NAC in patients meeting criteria for early discontinuation may be an effective treatment option in a sizeable proportion of individuals with potentially toxic acetaminophen ingestions.